The therapeutic effect in gliomas of nanobubbles carrying siRNA combined with ultrasound-targeted destruction - Cai W (Dove Medical Press, 2018)
Wenbin Cai,1,2,* Wei Lv,1,3,* Yang Feng,4 Hengli Yang,1 Yajun Zhang,1 Guodong Yang,5 Yunyou Duan,1 Jia Wang1 1Department of Ultrasound Diagnosis, Tang Du Hospital, Fourth Military Medical University, Xi’an 710038, China; 2General Hospital of Tibet Military Command, Lhasa, Tibet Autonomous Region, 850007, China; 3Department of Radiology, 305 Hospital of Chinese People’s Liberation Army, Xicheng District, Beijing, 100017, China; 4Xijing Hospital, Traditional Chinese Medicine, Xi’an 710032, China; 5Department of Biochemistry and Molecular Biology, The Fourth Military Medical University, Xi’an 710032, China *These authors contributed equally to this work Background: Nanobubbles (NBs) combined with ultrasound-targeted destruction (UTD) have become promising potential carriers for drug or siRNA delivery. Due to their nano-size, NBs could penetrate tumor blood vessels and accumulate in intercellular spaces so that “sonoporation” induced by UTD would act directly on the tumor cells to increase cell membrane permeability. Methods: Based on the successful the fabrication of NBs, we synthesized NBs carrying siRNA (NBs-siRNA) by using a biotin-streptavidin system. We then utilized ultrasound irradiation (UI)-targeted NBs-siRNA to improve siRNA transfection and achieve the inhibition of glioma growth.Results: NBs as carriers combined with UI effectively enhanced siRNA transfection and the effect of silencing targeted genes in vitro. Additionally, a better therapeutic effect was shown in the NBs-siRNA with UI group in vivo compared with that of microbubbles (MBs) with UI or NBs-siRNA without UI.Conclusion: These results indicated that NBs combined with UTD might be an ideal delivery vector for siRNA to achieve the noninvasive treatment of glioma. Keywords: nanobubbles, ultrasound, siRNA, glioma